ANALISIS PENGARUH EFISIENSI BIAYA, STRUKTUR PEMODALAN, DAN KUALITAS ASET SERTA TINGKAT INFLASI TERHADAP PROFITABILITAS BANK UMUM SYARIAH PERIODE 2013 – 2022 (Studi kasus pada bank umum syariah KBMI III) - Fajri, Muhammad; Ika Khusnia Anggraini (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Banking is one of the vital sectors that plays a role in the economic of a country. Bank Muamalat, Bank Panin Dubai Syariah, Bank BTPN Syariah, and Bank Mega Syariah are the four islamic banks in Indonesia, which have the opportunity to enchance their contriution to syariah product services to the Indonesian people. This study aims to analyze the influence of BOPO, NPF, CAR and Infation on ROE at Bank Muamalat, Bank Panin Dubai Syariah, Bank BTPN Syariah, and Bank Mega Syariah for the period 2013-2022. The method used in this research is quantitative with secondary data sourced from the official company website. Data is processed using panel data regression analysis. The results of this study indicate that BOPO, NPF, CAR, and Inflation simultaneously have a significant impact on ROE.